Symbolic Reverence: An Ethnographic Study on the Tonggoluan and Pusi’ Death Rituals Within Bolaang Mongondow Society Through Victor Turner's Perspective - Hasan, Faradila; Fadillah, Dinda; Willya, Evra; Sugitanata, Arif (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This ethnography study investigates the sociocultural significance of the Tonggoluan and Pusi’ death rituals that persist in Bolaang Mongondow society despite the threat of modernity. Current understanding ignores its ontological role in preserving the existence of Bolaang Mongondow, so this research aims to explain these traditions as a basis for identity formation and social reproduction through the lens of Victor Turner's symbolic anthropology. Using a rigorous ethnographic field study, data was collected through in-depth interviews and observation of six elders in Bolaang Mongondow. These findings reveal that Tonggoluan graves encapsulate the eternal spiritual connection between living and deceased ancestors. Its sacralization reflects a strong belief in a metaphysical realm that upholds the collective memory of this community. Meanwhile, wearing Pusi’ mourning clothes symbolizes sadness and passing down cultural values from generation to generation. This ritual also builds communal solidarity during mourning, reaffirming Bolaang Mongondow's identity. Essentially, these two traditions combine the temporary and the eternal through the creative reproduction of meaning, forming the basis of local existence. Therefore, maintaining this death ceremony amidst the erosion of modern culture is very important to ensure the continuity of the unique identity of this indigenous community. This encourages a deeper global appreciation of the role of death rituals in strengthening the cultural vitality of the Bolaang Mongondow community group.